Metabolic and performance responses to constant-load vs. variable-intensity exercise in trained cyclists - Palmer, G. S.; Borghouts, L. B.; Noakes, T. D.; Hawley, J. A. (Journal of Applied Physiology, 1999)
We studied glucose oxidation (Glu(ox)) and glycogen degradation during 140 min of constant-load [steady-state (SS)] and variable-intensity (VI) cycling of the same average power output, immediately followed by a 20-km performance ride [time trial (TT)]. Six trained cyclists each performed four trials: two experimental bouts (SS and VI) in which muscle biopsies were taken before and after 140 min of exercise for determination of glycogen and periodic acid-Schiff's staining; and two similar trials without biopsies but incorporating the TT. During two of the experimental rides, subjects ingested a 5 g/100 ml [U-(14)C]glucose solution to determine rates of Glu(ox). Values were similar between SS and VI trials: O(2) consumption (3.08 +/- 0.02 vs. 3.15 +/- 0.03 l/min), energy expenditure (901 +/- 40 vs. 904 +/- 58 J x kg(-1) x min(-1)), heart rate (156 +/- 1 vs. 160 +/- 1 beats/min), and rating of perceived exertion (12.6 +/- 0.6 vs. 12.7 +/- 0.7). However, the area under the curve for plasma lactate concentration vs. time was significantly greater during VI than SS (29.1 +/- 3.9 vs. 24.6 +/- 3. 7 mM/140 min; P = 0.03). VI resulted in a 49% reduction in total muscle glycogen utilization vs. 65% for SS, while total Glu(ox) was higher (99.2 +/- 5.3 vs. 83.9 +/- 5.2 g/140 min; P < 0.05). The number of glycogen-depleted type I muscle fibers at the end of 140 min was 98% after SS but only 59% after VI. Conversely, the number of type II fibers that showed reduced periodic acid-Schiff's staining was 1% after SS vs. 10% after VI. Despite these metabolic differences, subsequent TT performance was similar (29.14 +/- 0.9 vs. 30.5 +/- 0.9 min for SS vs. VI). These results indicate that whole body metabolic and cardiovascular responses to 140 min of either SS or VI exercise at the same average intensity are similar, despite differences in skeletal muscle carbohydrate metabolism and recruitment.